Childhood, street and survival: The case of La Paz and El Alto (Bolivia) - Cavagnoud, Robin (2015)
Children out of family relationships enter the world of street and socialize with groups of peers with whom they share daily activities like work, theft and alcohol and inhalants consumption. Their lives are commonly associated with survival. However, the study of their life courses shows that the use ofthis term is not always adequate. Following implementation of supports and forms of stability that children reach to maintain with peers and associations, survival gives way to a relative control, random but real, of their destiny. From a fieldwork in La Paz and El Alto (Bolivia) with observations and children life stories in street situation, the article highlights transitions to and out of survival in their biographical course to characterize this notion.